Evaluation of galectin-3 and titin in cats with a sarcomeric gene mutation associated with echocardiography - Kanokwan Demeekul; Pratch Sukumolanan; Soontaree Petchdee (Veterinary World, 2024)
Background and Aim: Cardiac biomarkers, such as serum galectin-3 (Gal-3) and titin levels, may be related to cats with sarcomeric gene mutations. This study evaluated cardiac biomarkers and echocardiographic parameters in cats with or without myosin-binding protein C3 (MYBPC3) gene mutations.